Fluktuasi Populasi Lalat Buah Bactrocera spp. (Diptera : Tephritidae) pada Pertanaman Cabai Merah (Capsicum Annuum) di Kabupaten Bandung, Jawa Barat - Agus Susanto; Yadi Supriyadi; Tohidin Tohidin; Nenet Susniahti; Vickri Hafizh (Agrikultura, 2017)
ABSTRACTFluctuation population of fruit flies Batrocera spp. (Dipthera: Tephritidae) on chilli (Capsicum annuum) plantation areas in Bandung Regency, West JavaFruit flies (Bactrocera spp.) are destructive pest that cause damages to horticulture commodities such as fruits and vegetables. The purpose of this study was to investigate fluctuation population of fruit flies in relation to abiotic factors, such as temperature, rainfall, number of rainy days, and biotic factors, such as host phenology and natural enemies. The field experiment was conducted in Pulosari Village, Pangalengan, Bandung. This research used survey method by placing 20 fruit flies traps on host plants, in which 10 traps were being placed in the outside and the others were being placed in the inside within 10 meters distance per trap. Trapped flies were collected and their population was counted in every week. The results revealed that abiotitic factors (temperature, rainfall, number of rainy days) have non significant influence indicated by the regression analysis of each temperature (Y=-101.2+2298.7x; R2=0.253; P>0.05), rainfall (Y= 0.143+154.4x; R2 = 0.004; P> 0.05), and the number of rainy days (Y= 6.607+140.51x; R2 = 0.015; P>0.05). Meanwhile, fruit fly with the dominant population was Bactocera dorsalis which was included into sibling species of Bactrocera dorsalis Complex with number of population was 93% from specimen sample.Keywords: Fluctuation population, fruit flies, Batrocera dorsalis Complex, ChilliABSTRAKLalat buah (Bactrocera spp.) merupakan hama penting yang menyerang tanaman hortikultura baik buah-buahan ataupun sayuran buah. Penelitian ini bertujuan untuk mengetahui korelasi fluktuasi populasi lalat buah pada pertanaman cabai merah terhadap faktor abiotik berupa suhu, curah hujan, jumlah hari hujan dan faktor biotik berupa fenologi tanaman inang dan musuh alami. Percobaan ini dilaksanakan di Desa Pulosari, Kecamatan Pangalengan Kabupaten Bandung. Percobaan dilakukan menggunakan metode survei dengan memasang perangkap lalat buah pada lahan pertanaman cabai merah sebanyak 20 perangkap dengan 10 perangkap bagian luar dan 10 perangkap bagian dalam dengan jarak antar perangkap 10 meter. Hasil tangkapan dikumpulkan dan dihitung populasi lalat buah yang terperangkap setiap minggunya. Hasil penelitian menunjukan faktor abiotik (suhu, curah hujan, jumlah hari hujan) tidak memberikan pengaruh signifikan ditunjukan dengan analisis regresi masing-masing pada suhu ( Y= -101,2+ 2298,7x ; R2=0,253; P > 0,05), Curah hujan (Y= 0,143 + 154,4x ; R2= 0,004 ; P > 0,05), dan Jumlah hari hujan (Y= 6,607 + 140,51x ; R2=0,015 ; P > 0,05) Sedangkan lalat buah yang memiliki populasi paling dominan adalah Bactrocera dorsalis yang termasuk sibling dari spesies Bactrocera dorsalis Kompleks dengan jumlah populasi sebanyak 93% dari sampel spesimen.Kata kunci : Fluktuasi populasi, Lalat buah, Bactrocera dorsalis Kompleks, Cabai merah